Pengaruh Inflasi terhadap Tingkat Pengembalian (Real Return) Deposito - Yanti Enjelika Hutasoit; Yanti Octacia Selvianica Sigalingging; May Artha Pakpahan; Sastri Erpina Sinaga; Hamonangan Siallagan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to examine the effect of inflation on deposit development using a literature review approach. Data were obtained from previous empirical studies, academic books, official reports, and other relevant scientific publications related to inflation and banking performance. The analysis indicates that inflation has a significant influence on the real return of bank deposits. When inflation increases and exceeds the interest rates offered by banks, the real yield on deposits becomes negative, thereby reducing their attractiveness as a savings and store-of-value instrument. Under such conditions, depositors tend to reallocate their funds to alternative investment instruments, such as gold, bonds, or stocks, which are perceived to provide better protection against inflation. This shift in investment behavior can lead to a decline in deposit growth and reduce banks’ third-party funds (DPK), potentially affecting banking liquidity and financial stability. The findings emphasize that inflation is a crucial macroeconomic variable that shapes saving behavior, influences deposit mobilization, and determines the stability of banking funding sources. Therefore, maintaining price stability is essential to support sustainable deposit growth and strengthen the resilience of the banking sector.